Implementation of Tsunami Evacuation Maps at Setubal Municipality, Portugal - Santos, Angela (2018)
The Setubal municipality, Portugal, has diversified land use along its coastline (mostly located in a low-lying area): on the west there are beaches; the centre is dominated by a densely populated downtown; and the east has an important industrial area. Although the seismic activity in mainland Portugal is moderate, considering the variety of exposed elements, the objectives of this study are to present and discuss the implementation of tsunami evacuation maps at Setubal municipality. Thus, tsunami numerical modelling was carried out by considering the 1969 tsunami and the 1755 tsunami scenarios. The model results show that the first tsunami wave arrived within 30–40 min of the earthquake. The inundation depth was up to 9 m at the beaches, 4.9 m downtown, and 4.0 m in the industrial area. These velocities are too dangerous if beach users are caught by the tsunami waves, even in a moderate scenario. Therefore, coastal communities must evacuate the inundated zones to high ground before the arrival of the first tsunami wave. For this reason, tsunami evacuation maps were created, indicating the quickest and safest routes to the meeting points, located on high ground and outside of the inundation zones.